Inżynieria rolnicza a zrównoważony rozwój obszarów wiejskich - Pawlak, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Current tasks for the agricultural engineering have been presented. An attempt to describe the interrelations between agricultural engineering and the sustainable development of agriculture has been undertaken. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 77-83